2013
DOI: 10.1111/dth.12085
|View full text |Cite
|
Sign up to set email alerts
|

Oral retinoids and plasma lipids

Abstract: Retinoids and rexinoids are prescribed for conditions ranging from acne vulgaris to hyperkeratosis to cutaneous T cell lymphoma. Dyslipidemia is a frequent consequence of the use of these drugs, with more than one-third of patients manifesting aberrations in triglyceride (TG) levels. The efficacy of retinoic acid derivatives is linked to their influence on lipid metabolism in the skin, which can impair systemic lipid trafficking and metabolism in some patients. Thus, baseline screening for preexisting dyslipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
(41 reference statements)
2
16
0
1
Order By: Relevance
“…These findings led to the identification of a novel effect of atRA signaling in the liver. The indication of the proteomic study that atRA alters lipid and fatty acid metabolism was intriguing, because use of retinoids and RA isomers isotretinoin (13-cisRA) and alitretinoin (9-cisRA) in dermatology and in cancer treatment is associated with changes in lipid and lipoprotein metabolism, including hypertriglyceridemia, hypercholesterolemia, increased total cholesterol, and decreased high-density lipoprotein-cholesterol in about one-third of the treated patients (Lawrence et al, 2001;Staels, 2001;Brelsford and Beute, 2008;Lilley et al, 2013). The induction of SREBP1 mRNA observed in this study after treatment with 10 mM atRA is in agreement with the clinical findings, as the 10 mM atRA treatment closely mimics the RA exposures observed after retinoid therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings led to the identification of a novel effect of atRA signaling in the liver. The indication of the proteomic study that atRA alters lipid and fatty acid metabolism was intriguing, because use of retinoids and RA isomers isotretinoin (13-cisRA) and alitretinoin (9-cisRA) in dermatology and in cancer treatment is associated with changes in lipid and lipoprotein metabolism, including hypertriglyceridemia, hypercholesterolemia, increased total cholesterol, and decreased high-density lipoprotein-cholesterol in about one-third of the treated patients (Lawrence et al, 2001;Staels, 2001;Brelsford and Beute, 2008;Lilley et al, 2013). The induction of SREBP1 mRNA observed in this study after treatment with 10 mM atRA is in agreement with the clinical findings, as the 10 mM atRA treatment closely mimics the RA exposures observed after retinoid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of multiple pathways by atRA likely leads to diverse effects on liver physiology, including altered lipid homeostasis. In humans both excessive intake of vitamin A or retinoids and vitamin A deficiency lead to hypertriglyceridemia, elevated total cholesterol, and decreased high-density lipoprotein cholesterol (Bershad et al, 1985;Lawrence et al, 2001;Staels, 2001;Brelsford and Beute, 2008;Lilley et al, 2013). However, likely because of a dichotomy of the effects of vitamin A on the liver, the endogenous role of atRA in regulating lipid and fatty acid homeostasis and role of atRA in liver disease is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…It also decreases lipoprotein lipase activity, which hydrolyzes triglycerides into fatty acids. 65 Peroxisome proliferator-activated receptors (PPARs) are nuclear hormone receptors that are part of the superfamily of receptors that also includes retinoid receptors and others. These receptors are strongly expressed in the skin and sebaceous glands and are involved in oxidative pathways for fatty acids.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…These receptors are strongly expressed in the skin and sebaceous glands and are involved in oxidative pathways for fatty acids. 65 Retinoic X receptors form heterodimers with PPARs and transactivation by rexinoids are believed to influence lipid metabolism. 1 Triglyceride elevation also is regulated by transactivation of LXR (Liver X receptor)/RXR heterodimers by sterol regulatory element-binding proteins, which are transcription regulators involved in cholesterol biosynthesis.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…One confounding factor for the use of LXR and RXR agonists in patients is the increase of triglycerides in plasma (Lilley et al, 2013; Tontonoz and Mangelsdorf, 2003). Interestingly, the only published clinical trial with LXR agonist reported adverse effects on CNS and not an increase of serum triglycerides (Katz et al, 2009).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%